Development of Dark Triad Scales for Machiavellianism, Psychopathy and Narcissism From the Hogan Development Survey - Coleman, Brendan; Dulewicz, Victor (Journal of Organizational Psychology, 2024)
Dark Triad personalities (DT: psychopathy, narcissism and Machiavellianism) adversely affect organisational functioning. There were three research questions: (1) Can DT personality measures be derived from the Hogan Development Survey (HDS)? (2) Will age, tenure, and gender moderate the relationships between the DT personality measures and job performance? (3) What are the relationships between scores on the DT personality measures? Four hypotheses were framed from the research questions and tested on a sample of 918 managers. Three new DT scales were derived from the HDS, using a mapping exercise based on Ferrell and Gaddis’s (2016) research findings. All scales showed acceptable Alpha reliabilities. The mapping exercise provided evidence of construct validity. An analysis of high scorers on pairings of the three DT scales showed divergent validity. Partial correlation results showed significant negative correlations between psychopathy, narcissism, Machiavellianism and job performance, demonstrating criterion validity. Organisations could use the new DT scale scores for screening applicants, for identifying future management potential and providing developmental feedback to employees.